Housework reduces all-cause and cancer mortality in Chinese men. - Ruby Yu (Public Library of Science (PLoS), 2013)
Background Leisure time physical activity has been extensively studied. However, the health benefits of non-leisure time physical activity, particular those undertaken at home on all-cause and cancer mortality are limited, particularly among the elderly. Methods We studied physical activity in relation to all-cause and cancer mortality in a cohort of 4,000 community-dwelling elderly aged 65 and older. Leisure time physical activity (sport/recreational activity and lawn work/yard care/gardening) and non-leisure time physical activity (housework, home repairs and caring for another person) were self-reported on the Physical Activity Scale for the Elderly. Subjects with heart diseases, stroke, cancer or diabetes at baseline were excluded (n = 1,133). Results Among the 2,867 subjects with a mean age of 72 years at baseline, 452 died from all-cause and 185 died from cancer during the follow-up period (2001-2012). With the adjustment for age, education level and lifestyle factors, we found an inverse association between risk of all-cause mortality and heavy housework among men, with the adjusted hazard ratio (HR) of 0.72 (95%CI = 0.57-0.92). Further adjustment for BMI, frailty index, living arrangement, and leisure time activity did not change the result (HR = 0.71, 95%CI = 0.56-0.91). Among women, however, heavy housework was not associated with all-cause mortality. The risk of cancer mortality was significantly lower among men who participated in heavy housework (HR = 0.52, 95%CI = 0.35-0.78), whereas among women the risk was not significant. Men participated in light housework also were at lower risk of cancer mortality than were their counterparts, however, the association was not significant. Leisure time physical activity was not related to all-cause or cancer mortality in either men or women. Conclusion Heavy housework is associated with reduced mortality and cancer deaths over a 9-year period. The underlying mechanism needs further study.